Solving Nonstiff Higher-Order Ordinary Differential Equations Using 2-Point Block Method Directly - Hazizah Mohd Ijam; Mohamed Suleiman; Norazak Senu; Ali Ahmadian; Soheil Salahshour; Ahmad Fadly Nurullah Rasedee (Hindawi Publishing Corporation, 2024)
We describe the development of a 2-point block backward difference method (2PBBD) for solving system of nonstiff higher-order ordinary differential equations (ODEs) directly. The method computes the approximate solutions at two points simultaneously within an equidistant block. The integration coefficients that are used in the method are obtained only once at the start of the integration. Numerical results are presented to compare the performances of the method developed with 1-point backward difference method (1PBD) and 2-point block divided difference method (2PBDD). The result indicated that, for finer step sizes, this method performs better than the other two methods, that is, 1PBD and 2PBDD.